Зміна реологічних властивостей суспензії лікарських і косметичних засобів під час подрібнення в бісерних млинах - Грінінг-Гера, Катерина Робертівна; Губеня, Олексій Олександрович (My University, 2023)
Реологічні властивості суспензій рицинової олії та суспензії для косметичних засобів на її основі під час подрібнення в бісерному млині у межах дослідженого діапазону залежно від тривалості вимірювань не змінюються. Залежність вʼязкості від швидкості зсуву під час подрібнення суспензії має степеневий характер і підтверджує неньютонівський характер. В’язкість змінюється логарифмічно для всіх значень температури і становить 1,011 Па‧с для рицинової олії та 2,127 Па‧с для суспензії на її основі. Суспензія має у 2,1 раза більшу в’язкість порівняно з рициновою олією, що пояснюється високим вмістом сухих речовин (40%) та збільшенням новоутвореної площі під час надтонкого подрібнення. Evaluation of rheological characteristics is an integral and important part of research on the creation of soft dosage forms, which affect such technological parameters of the systemas emuls ification, transportation, and also ensure proper consumer properties (spreadability, uniformdistribution and fixation on the surface. The rheological properties of drug and cosmetic s uspensions during grinding in a bead mill were studied. The suspension was prepared according to the recipe: pigment iron oxide red 120 — 40% and castor oil — 60%. The duration of grinding is 45 minutes (2700 s). During grinding, the bead mill chamber was sampled every 5 minutes (300 s) and the shear stress at different values of the shear rate was measured. Rheological characteristics – viscosity and shear stress were studied on a rotary viscometer. The flow curves of castor oil and suspension were constructed and it was established that, based on it, within the studied range, the nature of the flow does not change depending on the duration of the measurements. The analysis of the suspension curve during grin - ding revealed features that explain the formation and the structure formation. The dependence of effective viscosity on the shear rate when grinding the suspension has a power-law character and con - firms the non-Newtonian nature and is defined as a linear plastic body. The temperature dependence of the effective viscosity of castor oil and suspension was compared. The viscosity of both tested substances varies logarithmically for all investigated temperature values and is equal to 1,011 Pa‧s for castor oil, which corresponds to the value in the manufacturerʼs specification, and 2,127 Pa‧s for the suspension based on castor oil. The suspension under study has 2,1 times higher viscosity compared to castor oil, according to the high content of solids (40%) and the increase in the newly formed area during the ultrafine grinding process. The obtained results of research on the rheological properties of the suspension allow us to monitor and adjust the parameters of ultrafine grinding process for achieving the required product quality.
Keywords: кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв; бісерний млин; рицинова олія; реологія суспензій; bead mill; suspension; rheology